2018
DOI: 10.1038/s41598-018-19763-7
|View full text |Cite
|
Sign up to set email alerts
|

Serum miR-375-3p increase in mice exposed to a high dose of ionizing radiation

Abstract: Exposure to high-doses of ionizing radiation (IR) leads to development of a strong acute radiation syndrome (ARS) in mammals. ARS manifests after a latency period and it is important to develop fast prognostic biomarkers for its early detection and assessment. Analysis of chromosomal aberrations in peripheral blood lymphocytes is the gold standard of biological dosimetry, but it fails after high doses of IR. Therefore, it is important to establish novel biomarkers of exposure that are fast and reliable also in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 44 publications
2
20
0
Order By: Relevance
“…Thus, their expression relates to cancer tissue growth or distant metastasis. We have previously reported that during the active release of EVs to blood flow after exposure to higher dose of ionizing radiation, the lower accumulation of EV components in their original tissue cells was observed in comparison to the other tissues with non-active release of EVs (27,28). Our case data showed that the concentration of nSMase co-expressed with HER2 in 1st recurrent cancer tissue, where the levels of both are lower than in primary cancer tissue (Fig.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Thus, their expression relates to cancer tissue growth or distant metastasis. We have previously reported that during the active release of EVs to blood flow after exposure to higher dose of ionizing radiation, the lower accumulation of EV components in their original tissue cells was observed in comparison to the other tissues with non-active release of EVs (27,28). Our case data showed that the concentration of nSMase co-expressed with HER2 in 1st recurrent cancer tissue, where the levels of both are lower than in primary cancer tissue (Fig.…”
Section: Discussionsupporting
confidence: 53%
“…These responses suggested that recurrent cancer tissues more easily release EVs to peripheral blood serum and promote cancer progression and expansion. Thus, one reported mechanism is the transfer of miRNAs via exosomes from cancer cells to microenvironmental cells, promoting angiogenesis (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that miR-375-3p increases in the serum of mice exposed to 7 Gy X-rays causing cytotoxicity in pancreatic β cells (2). However, the direct relationship between miR-375-3p level increases in the blood and the cytotoxicity caused by 7 Gy irradiation remained to be clarified.…”
Section: Discussionmentioning
confidence: 97%
“…MicroRNAs (miRNAs) are small (18-25 nucleotides) non-coding RNA harboring a post-transcriptional gene regulatory function (1). Currently, miRNAs have been detected in various body fluids, including serum (2), plasma (3), urine (4), cerebrospinal fluid (5), breast milk (6), saliva (7), bronchoalveolar lavage fluid (8), ascites (9), and pleural effusion (10). Noteworthy, miRNAs are stable under non-physiological conditions, whether in body fluids or culture media.…”
Section: Introductionmentioning
confidence: 99%
“…Chiba et al indicated that miR-375-3p is significantly increased following exposure to 7 Gy of IR, and the authors suggested that this miRNA can serve as a predictor of DNA damage induced by IR. 30 Interestingly, following secretion from targeted cells, miRNAs packaged in exosomes can move to a remote distance to influence cell functions and modify the niche and host reaction in targeted or nontargeted cells, which leads to the bystander effect. Our previous study indicated that miR-7-5p packaged in exosomes from 2-Gy-irradiated human bronchial epithelial BEP2D cells induced bystander autophagy in nonirradiated BEP2D cells, and this autophagy was associated with the EGFR/Akt/mTOR signalling pathway.…”
Section: Introductionmentioning
confidence: 99%